Menguatkan Identitas: Rebranding Sebagai Jalan UMKM Desa Naik Kelas - Kusumowardhono, Broto Seno Kusumowardhono; Lussy Sulistiyowati, Eka; Niswatul Khasanah, Dwi; Ardevano, Kavindo; Salsa Arifana, Nabila; Faiz Hidayatulloh, Muhammad (Yayasan Dekhalisha Global Prestise, 2026)
Village-based Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in sustaining local economies while simultaneously preserving the continuity of cultural wisdom and identity. Nevertheless, in an era of global competition and digital transformation, numerous village MSMEs encounter substantial constraints in establishing a strong business image and expanding their market reach. This article examines rebranding strategies as an endeavour to consolidate business identity while concurrently enhancing the competitiveness of village MSMEs. Rebranding is not merely construed as the replacement of logos or packaging, but rather as a comprehensive process of reasserting the values, narratives, and local distinctiveness that differentiate these products from competitors. Through a literature review and descriptive qualitative approach, this article delineates the strategic steps of rebranding, encompassing market analysis, visual identity reinforcement, product storytelling, and the utilisation of digital technology. The community service activities were implemented through socialisation programmes, brand design training, and guided digital content creation for MSME practitioners in partner villages. Rebranding has been demonstrated to yield significant positive outcomes, including an enhanced professional image, expanded market access, and a heightened sense of community pride toward locally produced goods. Accordingly, rebranding constitutes a critical instrument in facilitating the upward trajectory of village MSMEs as integral components of the national creative economy ecosystem.